CpG island clones from a deletion encompassing the gene for adenomatous polyposis coli. - Varesco, L (1989)
Adenomatous polyposis coli (APC), a dominantly inherited disorder, has been mapped to chromosome 5q15-q21 by family linkage studies. Cells from patients with deletions in this region, in one case associated with polyposis in a family, have been used to construct human hamster hybrid cell lines that retain either the normal or deleted chromosome 5. These lines have been used to identify markers from the region of the polyposis gene obtained by cloning the ends of 0.5- to 2-megabase BssHII fragments purified by pulsed-field gel electrophoresis. Three markers are described that map within the deletions and must therefore be close to the APC gene.